Detection on matrix induced composite failures. (22nd March 2021) - Huang, Zheng-Ming; Wang, Li-sheng; Jiang, Feng; Xue, Y.D.
Abstract: As most composite failures are caused by matrix failures, the detection on the latter is of fundamentally importance. This can be achieved only when the homogenized stresses of the matrix obtained from a micromechanics theory are converted into true values. Based on the true stress concept established by the author, the matrix induced composite failures are predicted in this paper. There are essentially two kinds of matrix failures, i.e., tensile or compressive failures, depending on whether the normal stress of the matrix on its failure surface is positive or negative. It has been found that the two kinds of failures correspond to different failure mechanisms. A matrix tensile failure takes place as though the matrix were without any fiber reinforcement, and a quadratic failure criterion developed from Mohr's law suffices to detect such a failure. On the other hand, a compressive failure surface of the matrix can only occur in parallel to the fiber direction, and a matrix compressive failure is controlled by its shear strength. A slippage failure criterion based on the maximum equivalent true shear stress is developed to assess a matrix compression induced composite failure. The input required has been reduced to minimum. Good correlation between predicted and measured failure envelopes of a number of composite systems confirms the efficiency of the proposed failure criteria. Graphical abstract: Image 1 Highlights: Detection on composite failures from its constituent failures is achieved once the constituent true stresses are obtained. Two versatile criteria are proposed for the matrix tensile and compressive failures. Only matrix tensile, compressive and shear strengths plus the transverse tensile strength of a UD composite are required.